Anxiety and Sexual Function of Pregnant Women - Riski Oktafia; Wahyu Arifatun Zulfiyah; Arif Wahyu Setyo Budi; Laarne Pontillas (Universitas Muhammadiyah Yogyakarta, 2022)
Background: Physical and psychological changes during pregnancy can affect sexual function. Sexual function during pregnancy decreases with increasing gestational age which affects the desire to have sexual activity. Anxiety is one of the psychological factors that can interfere with the sexual function of pregnant women.Objective: The purpose of this research is to find out the relationship between anxiety and sexual function during pregnancy.Methods: This study uses quantitative research methods and a cross-sectional design. A total of 62 samples of pregnant women in all trimesters in the Bantul Yogyakarta area used a purposive sampling technique. The instruments used in the study were the Perinatal Anxiety Screening Scale and Female Sexual Function Index questionnaires. The statistical test used is the Spearman Rank Correlation Test.Results: The Spearman Rank Correlation test showed p-value=0.000 and r=0.475 which indicated that there was a significant relationship between anxiety and sexual function in pregnant women with sufficient corrective power.Conclusion: Anxiety related to the condition of sexual function during pregnancy. Nurses are expected to be able to provide health education to married couples and motivate couples to obtain adequate information about sexuality during pregnancy.